Determination of visual axis of tiger grouper juveniles Epinephelus fuscoguttatus, to develop a demand feeding system - Nai , Tan Han; Leong, Seng Lim; Rian, Freddie Firdaus; Chung, Fan Liau; Mukai, Yukinori (2011)
In a demand feeding system, the fish turn on the switch of the feeder to get feed. In order to develop a demand feeding system with an infrared light sensor to which juvenile tiger grouper, Epinephelus fuscoguttatus visually respond, the visual acuity and visual axis of the juveniles were determined to obtain fundamental understanding of their vision. Three farmed juveniles were anaesthetized with MS222 and fixed in Bouin’s solution. The left retinae of each juvenile were cut into nine regions (Figure 1). The specimens were embedded in paraffin, cut into 6 μm thick tangential sections, and stained with haematoxylin-eosin. The density of cone cells (0.01mm2) in each region was counted in the stained sections. Visual acuity was calculated using cone cell densities and lens diameter. The highest cone density of each juvenile was 359 (bottom, B), 394 (temporal, T) and 380 cells/0.01mm2 (temporal, T) respectively. The estimated minimum separable angles of the highest density regions were 4.312×10-3, 3.661×10-3, 3.592×10-3 radian in each juvenile respectively. The estimated visual acuities were 0.068, 0.080 and 0.081 in those regions. These results showed that the visual axis of tiger grouper juveniles was in forward.